Toxic Tares: The Poisonous Weeds (zizania) in Matthew's Parable of the Tares (Matthew 13.24-30, 36-43) - Cousland, J. R. C. (New Testament studies, 2015)
This article examines the poisonous characteristics of Lolium Temulentum L., the weed that is generally identified with the tares (zizania) mentioned in Matthew's Parable of the Wheat and the Tares (Matt 13.24-30, 36-43). It identifies the weed, examines its pervasiveness in antiquity, as well as the nature and degree of its toxicity, and establishes that the tares of the Palestine of Jesus' day were likely poisonous. With this in mind, it considers whether the tares' toxicity is a factor in understanding the parable and its interpretation, concluding that it is very likely presupposed by both.